FETAL OUTCOMES IN PREGNANCIES COMPLICATED BY OLIGOHYDRAMNIOS- EXPERIENCE AT A TERTIARY CARE HOSPITAL - Zubaida Akhtar; Afridi, Fauzia; Saima Gilani (Journal of medical sciences (Peshawar, Pakistan), 2023)
OBJECTIVE: To find out the association between oligohydramnios and fetal outcome in terms of mode of delivery, the weight of the newborn baby, APGAR score at 1 and 5 minutes, and admission to the neonatology unit. MATERIALS & METHODS: This prospective cohort study was conducted in Obstetrics and Gynaecology Department, Khyber Teaching Hospital, Peshawar from 1st June 2017 to 31st May 2018. Patients with singleton pregnancy and cephalic presentation with a period of gestation of about 37 weeks or above were included using a purposive non-probability sampling technique. A sample of 100 patients in Group A (exposed) whose AFI was < 5 in the absence of other associated risk factors were compared to 100 matched groups of subjects in Group B (non-exposed) with AFI 5—18. Pregnant women with gestational age <37 weeks, fetal congenital abnormalities, and pregnancies with co-morbidities like PIH, and pre-eclampsia were excluded from the study. RESULTS: The result comparison shows that Group A has a higher rate of labor induction and cesarean section than Group B.  However, there was no statistically significant difference in the weight of the newborn, APGAR score at 1 and 5 minutes, and admission to the neonatology unit in both groups. CONCLUSION: Oligohydramnios is associated with a higher rate of induction of labor and cesarean section, but it does not affect the weight of newborn babies, APGAR score at 1 and 5 minutes, and admission of the newborn to the neonatology unit. Key Words: Oligohydramnios, Amniotic fluid, Cesarean section, Induction of labor, APGAR score, Perinatal outcome.